MAKE A MATCH TYPE COOPERATIVE LEARNING MODEL TO IMPROVE INDONESIAN LANGUAGE LEARNING OUTCOMES - Hamsiah, Andi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The aim of the research is to describe the application of the Make a Match type cooperative learning model in improving Indonesian language learning outcomes for fourth grade students at SD Inpres Mannuruki 1, Biringkanya District, Makassar. The approach used in this research is a descriptive qualitative approach, the type of research is Classroom Action Research (PTK) which is carried out in 2 cycles. Each cycle goes through four stages, namely planning, implementation, observation, and reflection. The focus of the research is the application of the Make a Match type cooperative learning model and Indonesian language learning outcomes. The research subjects were 28 class IV teachers and students. Data collection techniques are observation, tests, and documentation. The data analysis used is qualitative analysis and quantitative analysis. The teacher's teaching activities in cycle I were in the sufficient category, while in cycle II they were in the good category. Student learning activities in cycle I were in the poor category, while in cycle II were in the good category. The results of the study showed that the average value of learning outcomes in cycle I was in the poor category (incomplete), while in cycle II there was an increase in learning outcomes with the average student score is in the good category (complete) and has met the established Minimum Completeness Criteria (KKM). Thus, it can be concluded that through the implementation of the Make a Match type cooperative learning model, Indonesian language learning outcomes can be improved for fourth grade students at SD Inpres Mannuruki 1, Biringkanaya District, Makassar.